Enhanced bamboo-wood fiber board and method of processing the same
Patent Information
- Application Number
- CN202610288290.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-10
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-03-10
AI Technical Summary
[0004]然而,尽管现有技术及加工方法众多,目前的竹木纤维板材仍普遍存在一系列亟待解决的技术缺陷;第一,界面结合强度不足,纤维与树脂基体的结合多依赖物理嵌合或外加偶联剂,难以达到分子级别的完美融合,长期使用易发生界面剥离;第二,结构设计缺乏梯度优化,多为均质结构,无法实现性能在厚度方向上的梯度分布,导致材料性能与应力分布的匹配性差,热胀冷缩明显(膨胀率通常>0.5%),安装后易起拱、拔缝;第三,功能集成度低,产品功能较为单一,传统板材对电磁波的屏蔽效应往往影响室内Wi-Fi信号传输,且表面损伤难以自主修复;第四,耐热性与阻燃性不足,现有板材多采用普通PVC树脂,软化点较低(60-70℃),靠近热源易软化变形;阻燃等级多为B1级,且燃烧时易熔融滴落、产生浓烟,无法满足消防要求较高的场所使用;第五,防水性能有限,多数板材仅做表面覆膜防水,断面无有效封边或封边不致密,长期处于潮湿环境时易吸水、膨胀、分层,无法可靠用于厨卫、阳台等潮湿区域
[0038]1、通过细菌纤维素在竹纤维束表面的原位生长,形成与基体共价键连接的纳米纤维素晶须,使增强相与基体之间不存在明确的界面边界;同时,结合界面相容层设计,以及梯度界面理念,在界面相容层中引入梯度密度分布,使层间结合强度达到2.5MPa以上,界面剪切强度达15MPa以上,较传统竹纤维复合材料提升80%以上,从根本上解决了界面剥离问题;
Abstract
Description
Technical Field
[0001] This invention relates to the field of bamboo and wood fiberboard, specifically to reinforced bamboo and wood fiberboard and its processing method. Background Technology
[0002] Bamboo fiber refers to cellulose fibers extracted from bamboo. Based on different processing techniques, it is mainly divided into two categories: natural bamboo fiber and chemical bamboo pulp fiber. Natural bamboo fiber is extracted directly from bamboo using a combination of physical and chemical methods, fully preserving bamboo's natural antibacterial, bacteriostatic, and UV-resistant properties. Bamboo fiberboard, on the other hand, uses bamboo fiber, wood fiber, and other plant fibers as the matrix raw material, mixed with polymer resins or other adhesives, and manufactured through extrusion, molding, or hot pressing processes. This type of board is a green and environmentally friendly engineered wood product. With its advantages of renewable raw materials, easy installation, moisture and mildew resistance, and thermal and sound insulation, it has been widely used in interior wall coverings, ceilings, furniture manufacturing, and transportation interiors.
[0003] Currently, there are various processing methods for bamboo and wood fiberboard, with the mainstream technologies including the following: First, the co-extrusion composite method, which mixes bamboo and wood powder with PVC resin, calcium powder, and other additives, then extrudes it at high temperature using a twin-screw extruder, followed by cooling and shaping in a vacuum mold. This process has high production efficiency and is currently the mainstream production method for integrated wall panels. Second, the hot-press molding method, which involves applying adhesives to fiber raw materials, laying them into blanks, and then curing them into boards under high temperature and pressure. This method is commonly used to produce bamboo-based engineered wood panels such as bamboo mat plywood and bamboo curtain plywood. Third, the impregnation modification method, which involves vacuum dehydrating bamboo and wood materials, then immersing them in a permeating liquid, followed by high-pressure injection, high-temperature shaping, and continuous extrusion to improve the material's corrosion resistance and flame retardant properties. In addition, in recent years, research has emerged on glue-free bonding technologies such as dry hot-press bonding, which uses high temperature to melt lignin to act as an adhesive, achieving self-bonding of the fibers.
[0004] However, despite numerous existing technologies and processing methods, current bamboo and wood fiberboard still suffers from a series of technical defects that urgently need to be addressed. First, the interfacial bonding strength is insufficient; the bonding between fibers and the resin matrix largely relies on physical interlocking or the addition of coupling agents, making it difficult to achieve perfect fusion at the molecular level, and leading to easy interfacial delamination with long-term use. Second, the structural design lacks gradient optimization, often exhibiting homogeneous structures that fail to achieve a gradient distribution of performance along the thickness direction. This results in poor matching between material properties and stress distribution, significant thermal expansion and contraction (expansion rate typically >0.5%), and a tendency for arching and gapping after installation. Third, the functional integration is low, with relatively simple product functions. First, traditional wood-based panels often suffer from shielding effects on electromagnetic waves, affecting indoor Wi-Fi signal transmission, and surface damage is difficult to repair. Fourth, they lack sufficient heat resistance and flame retardancy. Most existing panels use ordinary PVC resin with a low softening point (60-70℃), making them prone to softening and deformation near heat sources. Their flame retardancy rating is mostly B1, and they easily melt and drip during combustion, producing dense smoke, which is unsuitable for use in areas with high fire safety requirements. Fifth, their waterproof performance is limited. Most panels only have a surface waterproof coating, with no effective edge sealing or weak sealing at the edges. When exposed to humid environments for extended periods, they easily absorb water, swell, and delaminate, making them unreliable for use in damp areas such as kitchens, bathrooms, and balconies. Therefore, developing an enhanced bamboo-wood fiberboard and its processing method that can fundamentally solve these defects has become a pressing technological bottleneck for the industry. Summary of the Invention
[0005] The purpose of this invention is to provide reinforced bamboo and wood fiberboard and its processing method to solve the problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] Reinforced bamboo and wood fiberboard, including composite materials formed in one piece from top to bottom:
[0008] The UV-resistant and wear-resistant composite surface layer is a co-extruded layer of acrylic resin and polyvinyl fluoride, with the surface modified by nano-silica, the surface hardness is not less than 3H, and the UV aging resistance level is not less than level 4.
[0009] A first interface compatibility layer is applied beneath the UV-resistant and abrasion-resistant composite surface layer.
[0010] A gradient-reinforced core layer is placed under the first interface compatibility layer. The gradient-reinforced core layer adopts a layered gradient ratio, with the ratio of bamboo fiber to wood fiber being 3:1, 2:1, and 1:1 respectively, from near the UV-resistant and wear-resistant composite surface layer to near the low-expansion stable bottom layer.
[0011] A second interface-compatible layer is placed beneath the gradient-enhanced core layer.
[0012] A low-expansion stabilizing underlayer is applied beneath the second interface compatibility layer. The low-expansion stabilizing underlayer is a composite layer of inorganic mineral powder and modified resin, and its dimensional change rate upon heating does not exceed 0.25%.
[0013] A signal modulation layer is embedded between the UV wear-resistant composite surface layer and the first interface compatibility layer, or embedded below the low-expansion stable bottom layer. The signal modulation layer has a periodic microstructure array or micropore structure and is configured to attenuate electromagnetic waves in the 2.4GHz-5.8GHz frequency band by no more than 20%.
[0014] A self-healing surface coating is applied to the surface of a UV-resistant and wear-resistant composite layer. The self-healing surface coating contains a microcapsule-encapsulated bio-based repair agent.
[0015] The raw material of the gradient-reinforced core layer includes bamboo fiber bundles that are in-situ grown and reinforced by biological methods. Nanocellulose whiskers are grown in situ on the surface of the bamboo fiber bundles to form a micro-nano hierarchical reinforcement structure. The nanocellulose whiskers grow directionally on the surface of the bamboo fiber bundles through an enzyme-mediated self-assembly process and form covalent bonds with the bamboo fiber bundle body.
[0016] The gradient-reinforced core layer has honeycomb-shaped directional reinforcing ribs inside, and the core layer adopts a closed-cell microbubble structure with a microbubble pore size of 3-15μm and a closed-cell rate of not less than 95%.
[0017] The entire board is formed by multi-layer co-extrusion, vacuum gradient foaming and online closed-loop edge sealing. There are no exposed pores on the cross-section, the water absorption rate is not higher than 0.5%, the flame retardant rating reaches GB 8624-2012 B1-A level and there is no melting dripping or dense smoke at high temperature.
[0018] Another object of the present invention is to provide a processing method for the above-described reinforced bamboo and wood fiberboard, comprising the following steps:
[0019] Step S1: In-situ biological growth enhancement treatment of bamboo fiber bundles
[0020] Bamboo is steam-exploded to obtain oriented bamboo fiber bundles, which are then bio-activated in a complex enzyme system of cellulase and xylanase to generate active functional groups on the surface of the bamboo fiber bundles. The activated bamboo fiber bundles are then placed in a fermentation medium containing cellulose-producing bacteria and cultured statically at 25-35℃ for 3-10 days to allow bacterial cellulose to grow in situ on the surface of the bamboo fiber bundles to form nano-cellulose whiskers, thus obtaining surface-reinforced bamboo fiber bundles.
[0021] Step S2: Raw material pretreatment and grading
[0022] The surface-reinforced bamboo fiber bundles and wood fibers obtained in step S1 are dried to a moisture content of no more than 0.8%; according to the ratios of 3:1, 2:1 and 1:1 for each layer of the gradient-reinforced core layer, the surface-reinforced bamboo fiber bundles, wood fibers, heat-resistant modified PP / PVC blended resin, nano boron nitride, basalt short fibers, halogen-free intumescent flame retardant and additives are mixed to obtain three sets of core layer mixtures.
[0023] Step S3: Multi-layer co-extrusion molding
[0024] The UV-resistant and wear-resistant composite surface material, the three core layer mixtures, the low-expansion stable bottom layer material, the first interface compatibility layer material, and the second interface compatibility layer material were added to six extruders respectively. The plasticizing temperature of each extruder was controlled as follows: surface layer 185-200℃, core layer 175-190℃, bottom layer 180-195℃, and interface compatibility layer 180-190℃. Through a multi-layer co-extrusion die, the surface layer, the first interface compatibility layer, the gradient-reinforced core layer, the second interface compatibility layer, and the bottom layer were compounded in a top-to-bottom order to achieve integral extrusion. The die temperature was controlled at 182-192℃.
[0025] Step S4: Vacuum gradient foaming and shaping
[0026] The extruded sheet is fed into a vacuum gradient foaming chamber, where segmented temperature-controlled foaming is used. The foaming temperature is 170-175℃, 160-165℃, and 150-155℃ from the inlet to the outlet, respectively, while the vacuum degree is controlled between -0.07 and -0.09 MPa, so that the core layer forms uniform closed-cell microbubbles and honeycomb reinforcing ribs. It is then sent to a cooling and shaping machine, where segmented cooling is used to eliminate internal stress, and the cooling temperature is gradually reduced from 25℃ to 15℃.
[0027] Step S5: Online closed-loop edge sealing
[0028] The hot-press melting edge sealing process is used to wrap and seal the edges of the board in a closed loop. The sealing temperature is 200-210℃ and the pressure is 0.3-0.5MPa to ensure that there are no exposed pores on the cross-section of the board.
[0029] Step S6: Signal modulation layer processing
[0030] Based on design requirements, one of the following methods can be used to process the signal modulation layer on the surface of the board:
[0031] Method A: A periodic microstructure array is prepared on the release film by printing or electroplating process, and then bonded to a predetermined position on the surface of the board during co-extrusion molding in step S3. After molding, the release film is peeled off to form a frequency-selective surface functional layer.
[0032] Method B: After step S5, a microporous structure is processed on the surface of the board using laser engraving technology. The laser power is 5-8W and the scanning speed is 10-15 mm / s to form a microporous structure layer.
[0033] Step S7: Apply self-healing surface coating
[0034] Bio-based coatings containing microencapsulated bamboo tar repair agents and photothermal conversion nanoparticles are sprayed or rolled onto the surface of the board, with a coating thickness of 50-150 μm, and dried and cured at 40-60℃.
[0035] Step S8: Surface modification and post-treatment
[0036] The surface of the board is coated with nano-silica and then UV cured. The curing time is 30-60 seconds, and the UV intensity is 80-100 mW / cm². 2 Then, the product is cut and inspected according to specifications to obtain the finished product.
[0037] Compared with the prior art, the beneficial effects of the present invention are:
[0038] 1. By in-situ growth of bacterial cellulose on the surface of bamboo fiber bundles, nano-cellulose whiskers covalently bonded to the matrix are formed, eliminating the clear interface boundary between the reinforcing phase and the matrix. Simultaneously, by combining the interface compatibility layer design and the gradient interface concept, a gradient density distribution is introduced in the interface compatibility layer, enabling the interlayer bonding strength to reach over 2.5 MPa and the interfacial shear strength to reach over 15 MPa, which is more than 80% higher than traditional bamboo fiber composite materials, fundamentally solving the interfacial delamination problem.
[0039] 2. The gradient-reinforced core layer features a 3:1, 2:1, and 1:1 layered gradient ratio, a multi-fiber composite reinforcement consisting of bamboo fiber, wood fiber, basalt short-cut fiber, and nano-boron nitride, along with honeycomb-shaped directional reinforcing ribs and closed-cell microbubble structures. Self-growing reinforced bamboo fiber bundles are also introduced as the core layer reinforcement phase, ensuring a static bending strength of no less than 35 MPa and an impact strength of no less than 10 kJ / m. 2 This represents a 20-30% improvement over existing reinforced boards, while maintaining a board density of 1.0-1.2 g / cm³. 3 This achieves a balance between high strength and lightweight design;
[0040] 3. The heat-resistant modified resin system, the addition of nano boron nitride, and the low-expansion stable bottom layer design, combined with gradient interface stress optimization, increase the heat resistance temperature of the board by 15-20℃, the softening point reaches above 80℃, and the heating dimensional change rate does not exceed 0.25%, which is more than 50% lower than the existing boards (>0.5%). After installation, it is not easy to arch, pull-out, or warp, and can be used in large-area and large temperature difference scenarios.
[0041] 4. The closed-cell microbubble structure with a closed-cell rate of not less than 95% and the online closed-loop edge sealing process ensure that the water absorption rate of the board does not exceed 0.5%. It can withstand boiling water immersion for 72 hours without expansion or delamination, and there are no exposed pores on the cross-section. It can be directly used in damp areas such as kitchens, bathrooms, and balconies, completely solving the defects of existing boards that are only waterproof on the surface and absorb water on the cross-section.
[0042] 5. Frequency-selective surface functional layer and micro-hole signal optimization layer: Two optional signal control layer structures are provided: The frequency-selective surface functional layer achieves frequency-selective transmission characteristics for electromagnetic waves in the 2.4GHz-5.8GHz band through a periodic microstructure array design, with an insertion loss of no more than 1.5dB in the passband; The micro-hole structure layer forms micro-holes through laser engraving, with a wireless signal attenuation rate of no more than 20%; Both can solve the pain points of traditional board material signal shielding and meet the electromagnetic environment control needs of smart homes;
[0043] 6. Bio-based self-healing coating and low-cost self-healing design: The bamboo tar repair agent is encapsulated in microcapsules with lignin sulfonate as the wall material, and photothermal conversion nanoparticles of graphene oxide or carbon nanotubes are introduced. Under near-infrared light, the microcapsules can be triggered to rupture, accelerating the repair process and achieving a repair efficiency of over 75%. Bamboo tar, as a by-product of bamboo processing, has natural antibacterial and antifungal properties and is highly environmentally friendly.
[0044] 7. A halogen-free intumescent flame retardant system composed of aluminum hydroxide, magnesium hydroxide and ammonium polyphosphate in a ratio of 2:2:1, combined with a bio-based resin matrix of vegetable oil-based unsaturated polyester, achieves B1-A level flame retardancy. During combustion, it forms a dense char layer with no dripping or dense smoke, meeting the needs of work equipment scenarios with high fire protection requirements.
[0045] 8. Bamboo fiber bundles are self-grown and reinforced, requiring no external chemical adhesives; the bio-based repair agent is derived from bamboo processing byproducts; the halogen-free flame retardant system contains no halogenated harmful substances; the multi-layer composite structure design reduces material usage; online closed-loop edge sealing reduces waste of scrap materials; the whole system achieves multi-level utilization of bamboo resources and environmental friendliness throughout the entire life cycle.
[0046] 9. The mature processes of multi-layer co-extrusion, vacuum gradient foaming, and online closed-loop edge sealing, combined with low-cost coating technology and biological culture process, form a complete process chain that can be implemented in segments, making it easy to upgrade and transform existing production lines and has extremely high market application value. Detailed Implementation
[0047] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0048] Example 1
[0049] Reinforced bamboo and wood fiberboard, including composite materials formed in one piece from top to bottom:
[0050] The UV-resistant and wear-resistant composite surface layer is a co-extruded layer of acrylic resin and polyvinyl fluoride, with the surface modified by nano-silica, the surface hardness is not less than 3H, and the UV aging resistance level is not less than level 4.
[0051] A first interface compatibility layer is applied beneath the UV-resistant and abrasion-resistant composite surface layer.
[0052] A gradient-reinforced core layer is placed under the first interface compatibility layer. The gradient-reinforced core layer adopts a layered gradient ratio, with the ratio of bamboo fiber to wood fiber being 3:1, 2:1, and 1:1 respectively, from near the UV-resistant and wear-resistant composite surface layer to near the low-expansion stable bottom layer.
[0053] A second interface-compatible layer is placed beneath the gradient-enhanced core layer.
[0054] A low-expansion stabilizing underlayer is applied beneath the second interface compatibility layer. The low-expansion stabilizing underlayer is a composite layer of inorganic mineral powder and modified resin, and its dimensional change rate upon heating does not exceed 0.25%.
[0055] A signal modulation layer is embedded between the UV wear-resistant composite surface layer and the first interface compatibility layer, or embedded below the low-expansion stable bottom layer. The signal modulation layer has a periodic microstructure array or micropore structure and is configured to attenuate electromagnetic waves in the 2.4GHz-5.8GHz frequency band by no more than 20%.
[0056] A self-healing surface coating is applied to the surface of a UV-resistant and wear-resistant composite layer. The self-healing surface coating contains a microcapsule-encapsulated bio-based repair agent.
[0057] The raw material of the gradient-reinforced core layer includes bamboo fiber bundles that are in-situ grown and reinforced by biological methods. Nanocellulose whiskers are grown in situ on the surface of the bamboo fiber bundles to form a micro-nano hierarchical reinforcement structure. The nanocellulose whiskers grow directionally on the surface of the bamboo fiber bundles through an enzyme-mediated self-assembly process and form covalent bonds with the bamboo fiber bundle body.
[0058] The gradient-reinforced core layer has honeycomb-shaped directional reinforcing ribs inside, and the core layer adopts a closed-cell microbubble structure with a microbubble pore size of 3-15μm and a closed-cell rate of not less than 95%.
[0059] The entire board is formed by multi-layer co-extrusion, vacuum gradient foaming and online closed-loop edge sealing. There are no exposed pores on the cross-section, the water absorption rate is not higher than 0.5%, the flame retardant rating reaches GB 8624-2012 B1-A level and there is no melting dripping or dense smoke at high temperature.
[0060] Example 2
[0061] This embodiment adds the following to embodiment 1:
[0062] The nanocellulose whiskers in situ grown on the surface of the bamboo fiber bundles have an aspect ratio of 50:1 to 200:1, a diameter of 5-30 nm, a length of 500-3000 nm, and a grafting density of 10-50 whiskers / μm on the surface of the bamboo fiber bundles. 2 .
[0063] The raw materials of the gradient-reinforced core layer, by weight, include: 28-38 parts of bamboo fiber bundles reinforced by in-situ biological growth, 12-22 parts of wood fiber, 32-42 parts of heat-resistant modified PP / PVC blend resin, 6-10 parts of nano boron nitride, 4-7 parts of basalt chopped fiber, 0.8-1.6 parts of crosslinking agent, 1.2-2.2 parts of composite heat stabilizer, 5-9 parts of halogen-free intumescent flame retardant, 0.3-0.7 parts of antioxidant, and 1.0-1.8 parts of interface compatibilizer.
[0064] The basalt short-cut fibers are 1.5-3.5 mm in length and 6-12 μm in diameter, and are surface-modified with a silane coupling agent; the halogen-free intumescent flame retardant is a compound system of aluminum hydroxide, magnesium hydroxide and ammonium polyphosphate, with a compounding ratio of 2:2:1.
[0065] The signal modulation layer includes two optional structures, specifically:
[0066] Structure A: A frequency-selective surface functional layer with a periodic microstructure array, wherein the periodic microstructure array includes a cross-shaped, square ring, or complementary open ring structure, the period size is 5-20 mm, and the metallization layer thickness is 5-20 μm;
[0067] Structure B: Microporous structure layer, containing micropores with a diameter of 20-50 μm, a pore size of 5-10 μm, and a micropore distribution density of 1000-2000 pores / cm². 2 .
[0068] The frequency-selective surface functional layer and the micro-hole signal optimization layer offer two optional signal control layer structures: the frequency-selective surface functional layer achieves frequency-selective transmission characteristics for electromagnetic waves in the 2.4GHz-5.8GHz band through a periodic microstructure array design, with an insertion loss of ≤1.5dB in the passband; the micro-hole structure layer forms microholes through laser engraving, with a wireless signal attenuation rate of no more than 20%; both can solve the pain points of traditional board-based signal shielding and meet the electromagnetic environment control needs of smart homes;
[0069] The self-healing surface coating contains a bamboo tar repair agent encapsulated in microcapsules. The microcapsules have a particle size of 5-20 μm and a wall material of lignin sulfonate. The self-healing surface coating also contains photothermal conversion nanoparticles, which are graphene oxide or carbon nanotubes, with a mass fraction of 0.1-1%, used to trigger microcapsule rupture under near-infrared light irradiation to accelerate the repair process.
[0070] Both the first and second interface compatibility layers are maleic anhydride-grafted polypropylene compatibility layers with a thickness of 0.08-0.15 mm. Both layers exhibit a gradient density distribution, with the density gradually decreasing outwards from the contact surface with the core layer, and the density gradient rate is 0.05-0.15 g / cm³. 3 / mm.
[0071] By in-situ growth of bacterial cellulose on the surface of bamboo fiber bundles, nano-cellulose whiskers covalently bonded to the matrix are formed, eliminating the clear interface boundary between the reinforcing phase and the matrix. Simultaneously, by combining the design of the interface compatibility layer and the concept of gradient interface, a gradient density distribution is introduced in the interface compatibility layer, enabling the interlayer bonding strength to reach more than 2.5 MPa and the interfacial shear strength to reach more than 15 MPa, which is more than 80% higher than that of traditional bamboo fiber composite materials, fundamentally solving the problem of interfacial delamination.
[0072] The gradient-reinforced core layer features a 3:1, 2:1, and 1:1 layered gradient ratio, a multi-fiber composite reinforcement consisting of bamboo fiber, wood fiber, basalt chopped fiber, and nano-boron nitride, along with honeycomb-shaped directional reinforcing ribs and closed-cell microbubble structures. Self-growing bamboo fiber bundles are also introduced as the core layer reinforcement phase, ensuring a static bending strength of no less than 35 MPa and an impact strength of no less than 10 kJ / m. 2 This represents a 20-30% improvement over existing reinforced boards, while maintaining a board density of 1.0-1.2 g / cm³. 3 This achieves a balance between high strength and lightweight design;
[0073] The heat-resistant modified resin system, the addition of nano boron nitride, and the low-expansion stable bottom layer design, combined with gradient interface stress optimization, increase the heat resistance temperature of the board by 15-20℃, the softening point reaches above 80℃, and the heating dimensional change rate does not exceed 0.25%, which is more than 50% lower than the existing boards (>0.5%). After installation, it is not easy to arch, pull-out, or warp, and can be used in large-area and large temperature difference scenarios.
[0074] The closed-cell microbubble structure with a closed-cell rate of not less than 95% and the online closed-loop edge sealing process ensure that the water absorption rate of the board does not exceed 0.5%. It can withstand boiling water immersion for 72 hours without expansion or delamination, and there are no exposed pores on the cross-section. It can be directly used in damp areas such as kitchens, bathrooms, and balconies, completely solving the defects of existing boards that are only waterproof on the surface and absorb water on the cross-section.
[0075] The frequency-selective surface functional layer and the micro-hole signal optimization layer offer two optional signal control layer structures: the frequency-selective surface functional layer achieves frequency-selective transmission characteristics for electromagnetic waves in the 2.4GHz-5.8GHz band through a periodic microstructure array design, with an insertion loss of no more than 1.5dB in the passband; the micro-hole structure layer forms microholes through laser engraving, with a wireless signal attenuation rate of no more than 20%; both can solve the pain points of traditional board-based signal shielding and meet the electromagnetic environment control needs of smart homes;
[0076] The bio-based self-healing coating and low-cost self-healing design utilize microcapsules encapsulating bamboo tar repair agents with lignin sulfonate as the wall material, and introduce photothermal conversion nanoparticles such as graphene oxide or carbon nanotubes. Under near-infrared light, the microcapsules can be triggered to rupture, accelerating the repair process and achieving a repair efficiency of over 75%. Bamboo tar, as a by-product of bamboo processing, has natural antibacterial and antifungal properties and is highly environmentally friendly.
[0077] A halogen-free intumescent flame retardant system composed of aluminum hydroxide, magnesium hydroxide and ammonium polyphosphate in a ratio of 2:2:1, combined with a bio-based resin matrix of vegetable oil-based unsaturated polyester, achieves B1-A level flame retardancy. During combustion, it forms a dense char layer with no dripping and no dense smoke, meeting the needs of work equipment scenarios with high fire protection requirements.
[0078] Bamboo fiber bundles are self-grown and reinforced without the need for external chemical adhesives; the bio-based repair agent is derived from bamboo processing byproducts; the halogen-free flame retardant system contains no harmful halogen substances; the multi-layer composite structure design reduces material usage; online closed-loop edge sealing reduces waste of scrap materials; and the overall system achieves multi-level utilization of bamboo resources and environmental friendliness throughout its entire life cycle.
[0079] The mature processes of multi-layer co-extrusion, vacuum gradient foaming, and online closed-loop edge sealing, combined with low-cost coating technology and biological culture process, form a complete process chain that can be implemented in segments, making it easy to upgrade and transform existing production lines and possessing extremely high market application value.
[0080] Example 3
[0081] This embodiment provides a processing method for the above-mentioned reinforced bamboo and wood fiberboard, including the following steps:
[0082] Step S1: In-situ biological growth enhancement treatment of bamboo fiber bundles
[0083] Bamboo is steam-exploded to obtain oriented bamboo fiber bundles, which are then bio-activated in a complex enzyme system of cellulase and xylanase to generate active functional groups on the surface of the bamboo fiber bundles. The activated bamboo fiber bundles are then placed in a fermentation medium containing cellulose-producing bacteria and cultured statically at 25-35℃ for 3-10 days to allow bacterial cellulose to grow in situ on the surface of the bamboo fiber bundles to form nano-cellulose whiskers, thus obtaining surface-reinforced bamboo fiber bundles.
[0084] Step S2: Raw material pretreatment and grading
[0085] The surface-reinforced bamboo fiber bundles and wood fibers obtained in step S1 are dried to a moisture content of no more than 0.8%; according to the ratios of 3:1, 2:1 and 1:1 for each layer of the gradient-reinforced core layer, the surface-reinforced bamboo fiber bundles, wood fibers, heat-resistant modified PP / PVC blended resin, nano boron nitride, basalt short fibers, halogen-free intumescent flame retardant and additives are mixed to obtain three sets of core layer mixtures.
[0086] Step S3: Multi-layer co-extrusion molding
[0087] The UV-resistant and wear-resistant composite surface material, the three core layer mixtures, the low-expansion stable bottom layer material, the first interface compatibility layer material, and the second interface compatibility layer material were added to six extruders respectively. The plasticizing temperature of each extruder was controlled as follows: surface layer 185-200℃, core layer 175-190℃, bottom layer 180-195℃, and interface compatibility layer 180-190℃. Through a multi-layer co-extrusion die, the surface layer, the first interface compatibility layer, the gradient-reinforced core layer, the second interface compatibility layer, and the bottom layer were compounded in a top-to-bottom order to achieve integral extrusion. The die temperature was controlled at 182-192℃.
[0088] Step S4: Vacuum gradient foaming and shaping
[0089] The extruded sheet is fed into a vacuum gradient foaming chamber, where segmented temperature-controlled foaming is used. The foaming temperature is 170-175℃, 160-165℃, and 150-155℃ from the inlet to the outlet, respectively, while the vacuum degree is controlled between -0.07 and -0.09 MPa, so that the core layer forms uniform closed-cell microbubbles and honeycomb reinforcing ribs. It is then sent to a cooling and shaping machine, where segmented cooling is used to eliminate internal stress, and the cooling temperature is gradually reduced from 25℃ to 15℃.
[0090] Step S5: Online closed-loop edge sealing
[0091] The hot-press melting edge sealing process is used to wrap and seal the edges of the board in a closed loop. The sealing temperature is 200-210℃ and the pressure is 0.3-0.5MPa to ensure that there are no exposed pores on the cross-section of the board.
[0092] Step S6: Signal modulation layer processing
[0093] Based on design requirements, one of the following methods can be used to process the signal modulation layer on the surface of the board:
[0094] Method A: A periodic microstructure array is prepared on the release film by printing or electroplating process, and then bonded to a predetermined position on the surface of the board during co-extrusion molding in step S3. After molding, the release film is peeled off to form a frequency-selective surface functional layer.
[0095] Method B: After step S5, a microporous structure is processed on the surface of the board using laser engraving technology. The laser power is 5-8W and the scanning speed is 10-15 mm / s to form a microporous structure layer.
[0096] Step S7: Apply self-healing surface coating
[0097] Bio-based coatings containing microencapsulated bamboo tar repair agents and photothermal conversion nanoparticles are sprayed or rolled onto the surface of the board, with a coating thickness of 50-150 μm, and dried and cured at 40-60℃.
[0098] Step S8: Surface modification and post-treatment
[0099] The surface of the board is coated with nano-silica and then UV cured. The curing time is 30-60 seconds, and the UV intensity is 80-100 mW / cm². 2 Then, the product is cut and inspected according to specifications to obtain the finished product.
[0100] Furthermore: the steam explosion treatment in step S1 is performed at a pressure of 1.5-2.5 MPa, with a holding time of 3-8 minutes and instantaneous pressure release; the cellulase activity in the composite enzyme system is 5000-10000 U / g, and the xylanase activity is 2000-5000 U / g; the cellulose-producing bacteria are *Acetobacter xylinum* or *Agrobacterium*.
[0101] In step S4, the foaming time in the vacuum gradient foaming chamber is 8-12 min, and the closed-cell rate is not less than 95%; in step S5, the width of the online closed-loop edge sealing is 1-2 mm, and the bonding strength between the edge sealing layer and the board body is not less than 2.0 MPa; in step S8, the amount of nano-silica spraying is 5-8 g / m². 2 .
[0102] I. Experimental Samples
[0103] 1. Sample Group
[0104] Group A prepared the reinforced bamboo and wood fiberboard of Example 2 using the processing method in Example 3; specifically, the reinforced bamboo and wood fiberboard has a thickness of 10 mm, a five-layer composite structure, including self-growing reinforced bamboo fiber bundles, a gradient core layer, a signal modulation layer, and a self-healing coating;
[0105] Group B consists of commercially available ordinary bamboo and wood fiberboard, with a thickness of 10 mm, a common single-layer structure, and PVC base.
[0106] Group C consists of existing reinforced bamboo fiberboard, specifically 10 mm thick, advertised as "reinforced" and reinforced with fillers;
[0107] Preparation parameters for Group A reinforced bamboo and wood fiberboard:
[0108] Bamboo fiber bundles were subjected to steam explosion (2.0 MPa, 5 min) + enzyme activation + culture with *Acetobacter xylodis* for 7 days to grow nanocellulose whiskers in situ.
[0109] Gradient core layer ratio: bamboo fiber: wood fiber = 3:1 (top layer), 2:1 (middle layer), 1:1 (bottom layer);
[0110] Raw material ratio: 32 parts self-grown reinforced bamboo fiber bundles, 18 parts wood fiber, 38 parts heat-resistant modified PP / PVC blended resin, 8 parts nano boron nitride, 5 parts basalt short chopped fiber, and 7 parts halogen-free intumescent flame retardant (aluminum hydroxide: magnesium hydroxide: ammonium polyphosphate = 2:2:1).
[0111] Interface compatibility layer: maleic anhydride-grafted polypropylene, 0.12 mm thick, gradient density design;
[0112] Signal modulation layer: frequency selective surface structure (cross-shaped array, period 12 mm);
[0113] Self-healing coating: Contains bamboo tar microcapsules (12μm) + 0.3% graphene oxide;
[0114] Molding process: Six-layer co-extrusion, vacuum gradient foaming (170→165→155℃) and online closed-loop edge sealing.
[0115] II. Test Items and Standards
[0116] Table 1
[0117] Test Project Test Standards Test equipment Test conditions Interface bonding strength GB / T 17657-2013 Universal testing machine interlayer peel test, tensile speed 2mm / min static bending strength GB / T 17657-2013 Universal testing machine Three-point bending, span 240 mm, loading speed 5 mm / min Impact resistance GB / T 1043.1-2008 Simply supported beam impact testing machine Unnotched specimen, pendulum energy 5J heating dimensional change rate GB / T 17657-2013 constant temperature drying oven and calipers Dry at 80℃ for 24 h, and measure the change in length. Water absorption rate GB / T 17657-2013 Thermostatic water bath and electronic balance Soak in water for 24 hours, then weigh and calculate. Boiling water resistance GB / T 17657-2013 Boiling water bath and observation Soak in boiling water at 100℃ for 72 hours and observe the changes in appearance. Flame retardant rating GB 8624-2012 Cone calorimeter Individual combustion test, observe molten droplets / flue gas Surface hardness GB / T 6739-2006 Pencil Hardness Tester Zhonghua Pencil Series, Maximum Hardness Measurement Wi-Fi signal attenuation YD / T 1643-2015 Spectrum analyzer and emission source 2.4GHz band, the board is placed between the transceiver antennas. Self-repair efficiency GB / T 30698-2014 Microscope and scratch instrument Scratch depth 20μm, near-infrared light irradiation for 5 minutes, repair rate measured.
[0118] III. Test Results and Data
[0119] 1. Interface bonding strength
[0120] Table 2
[0121] sample Interlayer bond strength (MPa) Interfacial shear strength (MPa) Destruction Mode Group A 2.82 16.3 The matrix fractured, but no interfacial delamination was observed. Group B 0.95 7.8 Completely stripped of the interface Group C 1.28 9.2 Partial interface stripping
[0122] Conclusion: The interlayer bonding strength of the reinforced bamboo and wood fiberboard of this invention is 197% higher than that of ordinary boards and 120% higher than that of existing reinforced boards; the interfacial shear strength is 77% higher than that of existing reinforced boards, reaching 16.3 MPa, proving that the "self-growing reinforcement + gradient interface compatibility layer" technology effectively solves the interfacial delamination problem.
[0123] 2. Mechanical properties
[0124] Table 3
[0125] sample Static bending strength (MPa) <![CDATA[Impact strength (kJ / m 2 )]]> <![CDATA[Density (g / cm 3 )]]> Group A 42.6 12.8 1.08 Group B 24.3 5.2 0.95 Group C 31.5 7.9 1.15
[0126] Conclusion: The static bending strength of the reinforced bamboo-wood fiberboard of this invention is 42.6 MPa, which is 75% higher than that of ordinary boards and 35% higher than that of existing reinforced boards; the impact strength is 12.8 kJ / m. 2 This represents a 146% improvement over standard boards and a 62% improvement over existing reinforced boards. The density is only 1.08 g / cm³. 3 Achieving high strength under these conditions demonstrates the significant synergistic effect of "gradient ratio, multi-fiber compound, honeycomb reinforcing ribs and closed-cell microbubbles".
[0127] 3. Dimensional stability
[0128] Table 4
[0129] sample Heating dimensional change rate (%) Softening point (°C) Group A 0.18 86 Group B 0.62 68 Group C 0.45 72
[0130] Conclusion: The heated dimensional change rate of the reinforced bamboo and wood fiber board of this invention is 0.18%, which is 71% lower than that of ordinary boards and 60% lower than that of existing reinforced boards; the softening point is 86℃, which is 26% higher than that of ordinary boards and 19% higher than that of existing reinforced boards. This proves that "nano boron nitride, heat-resistant modified resin, low-expansion underlayer and gradient interface stress optimization" effectively improve thermal stability.
[0131] 4. Waterproof performance
[0132] Table 5
[0133] sample Water absorption rate (%) State after soaking in boiling water for 72 hours Group A 0.32 No expansion, no delamination, no cracking, and the cross-section is dry. Group B 2.85 Severe expansion, delamination, and edge cracking Group C 1.62 Slight swelling, edges turn white due to water absorption.
[0134] Conclusion: The water absorption rate of the reinforced bamboo and wood fiberboard of this invention is 0.32%, which is 89% lower than that of ordinary boards and 80% lower than that of existing reinforced boards; it remains intact after being soaked in boiling water for 72 hours, proving that the "closed-cell microbubble structure (closed-cell rate ≥95%) and online closed-loop edge sealing" achieve true whole-body waterproofing.
[0135] 5. Flame retardant properties
[0136] Table 6
[0137] sample Flame retardant rating Combustion phenomenon Smoke Density Rating (SDR) Group A B1-A Grade No dripping or thick smoke was observed, resulting in the formation of a dense carbon layer. 32 Group B B2 level Molten dripping, thick smoke 85 Group C B1 level Slight dripping, with smoke 58
[0138] Conclusion: The reinforced bamboo and wood fiberboard of this invention meets the GB 8624-2012 B1-A grade (the highest home decoration grade). It produces no dripping or thick smoke during combustion, proving that the "aluminum hydroxide: magnesium hydroxide: ammonium polyphosphate = 2:2:1 compound" forms a highly efficient expansion and char formation system.
[0139] 6. Electromagnetic signal modulation performance
[0140] Table 7
[0141] sample 2.4GHz signal attenuation rate (%) Passband insertion loss (dB) Group A - Structure A 15.3 (attenuation rate) 1.2 Group A - Structure B 18.6 (attenuation rate) - Group B 48.5 4.2 Group C 42.3 3.8
[0142] Conclusion: The two signal modulation structures of the reinforced bamboo and wood fiber board of this invention can control the signal attenuation rate to below 20%. The insertion loss of structure A (frequency selective surface) is only 1.2dB, which is 69% lower than that of ordinary boards and 68% lower than that of existing reinforced boards, thus completely solving the problem of traditional boards blocking Wi-Fi signals.
[0143] 7. Electromagnetic signal modulation performance
[0144] Table 8
[0145] sample Initial scratch depth (μm) Depth after repair (μm) Repair efficiency (%) Group A 20 4.2 79 Group B 20 20 0 Group C 20 20 0
[0146] Conclusion: The enhanced bamboo and wood fiberboard of this invention achieved a repair efficiency of 79% after 5 minutes of near-infrared light irradiation, proving that the "bamboo tar microcapsule and graphene oxide photothermal conversion" technology effectively realizes intelligent repair of surface damage.
[0147] 8. Electromagnetic signal modulation performance
[0148] Table 9
[0149] sample Surface hardness (H) UV aging resistance rating (1000h) Group A 3H Level 4 Group B 1H Level 2 Group C 2H Level 3
[0150] Conclusion: The surface hardness of the enhanced bamboo and wood fiber board of this invention reaches 3H and the UV aging resistance level is 4, proving that "nano-silica modification and UV curing" effectively improves surface performance.
[0151] IV. Comprehensive Comparison of Data
[0152] Table 10
[0153] Group A Group B Group C Group A improved compared to Group B. Group A improved compared to Group C. Interlayer bond strength (MPa) 2.82 0.95 1.28 +197% +120% Interfacial shear strength (MPa) 16.3 7.8 9.2 +109% +77% Static bending strength (MPa) 42.6 24.3 31.5 +75% +35% <![CDATA[Impact strength (kJ / m 2 )]]> 12.8 5.2 7.9 +146% +62% Heating dimensional change rate (%) 0.18 0.62 0.45 -71% -60% Softening point (°C) 86 68 72 +26% +719% Water absorption rate (%) 0.32 2.85 1.62 -89% -80% Flame retardant rating B1-A B2 B1 - - Combustion droplets none have slight - - Wi-Fi attenuation rate (%) 15.3 48.5 42.3 -68% -64% Self-repair efficiency (%) 79 0 0 - - Surface hardness (H) 3H 1H 2H - - <![CDATA[Density (g / cm 3 )]]> 1.08 0.95 1.15 Only +13% -6%
[0154] Therefore, the reinforced bamboo and wood fiberboard of this invention significantly outperforms existing ordinary boards and existing reinforced boards in all test items, achieving a breakthrough improvement in core performance indicators:
[0155] Interfacial bonding strength: The interlayer bonding strength reached 2.82 MPa, which is 120% higher than the existing reinforced type; the interfacial shear strength was 16.3 MPa, which is 77% higher; proving that the "self-growth reinforcement" technology has achieved essential interface reinforcement.
[0156] Mechanical properties: static bending strength 42.6MPa, impact strength 12.8 kJ / m², which are 35% and 62% higher than existing reinforced types, respectively, with a density of only 1.08g / cm³; proving that the synergistic reinforcement effect of "gradient ratio + multi-fiber compound + honeycomb reinforcing ribs + closed-cell microbubbles" is significant.
[0157] Dimensional stability: The heating dimensional change rate is 0.18%, and the softening point is 86℃, which are 60% and 19% higher than the existing reinforced type, respectively; proving that "nano boron nitride + low expansion substrate + gradient interface stress optimization" is effective;
[0158] Waterproof performance: Water absorption rate of 0.32%, and it can withstand boiling water immersion for 72 hours without damage, which is 80% lower than the existing reinforced type; proving that "closed-cell microbubble structure + online closed-loop sealing" achieves full-body waterproofing;
[0159] Flame retardant performance: reaches B1-A level, with no dripping or dense smoke; proving that the "2:2:1 compound halogen-free intumescent flame retardant system" forms a highly efficient char layer;
[0160] Electromagnetic control: Wi-Fi signal attenuation rate reduced to 15.3%, a 64% reduction compared to existing enhanced versions; demonstrating that the "frequency-selective surface functional layer" enables intelligent electromagnetic control;
[0161] Self-healing performance: Repair efficiency reaches 79%; proving that "bamboo tar microcapsules + photothermal conversion" achieves intelligent surface repair.
[0162] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0163] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A reinforced bamboo-wood fiberboard, characterized in that, Including composite materials formed in one piece from top to bottom: The UV-resistant and wear-resistant composite surface layer is a co-extruded layer of acrylic resin and polyvinyl fluoride, with the surface modified by nano-silica, the surface hardness is not less than 3H, and the UV aging resistance level is not less than level 4. A first interface compatibility layer is applied beneath the UV-resistant and abrasion-resistant composite surface layer. A gradient-reinforced core layer is placed under the first interface compatibility layer. The gradient-reinforced core layer adopts a layered gradient ratio, with the ratio of bamboo fiber to wood fiber being 3:1, 2:1, and 1:1 respectively, from near the UV-resistant and wear-resistant composite surface layer to near the low-expansion stable bottom layer. A second interface-compatible layer is placed beneath the gradient-enhanced core layer. A low-expansion stabilizing underlayer is applied beneath the second interface compatibility layer. The low-expansion stabilizing underlayer is a composite layer of inorganic mineral powder and modified resin, and its dimensional change rate upon heating does not exceed 0.25%. A signal modulation layer is embedded between the UV wear-resistant composite surface layer and the first interface compatibility layer, or embedded below the low-expansion stable bottom layer. The signal modulation layer has a periodic microstructure array or micropore structure and is configured to attenuate electromagnetic waves in the 2.4GHz-5.8GHz frequency band by no more than 20%. A self-healing surface coating is applied to the surface of a UV-resistant and wear-resistant composite layer. The self-healing surface coating contains a microcapsule-encapsulated bio-based repair agent. The raw material of the gradient-reinforced core layer includes bamboo fiber bundles that are in-situ grown and reinforced by biological methods. Nanocellulose whiskers are grown in situ on the surface of the bamboo fiber bundles to form a micro-nano hierarchical reinforcement structure. The nanocellulose whiskers grow directionally on the surface of the bamboo fiber bundles through an enzyme-mediated self-assembly process and form covalent bonds with the bamboo fiber bundle body. The gradient-reinforced core layer has honeycomb-shaped directional reinforcing ribs inside, and the core layer adopts a closed-cell microbubble structure with a microbubble pore size of 3-15μm and a closed-cell rate of not less than 95%. The entire board is formed by multi-layer co-extrusion, vacuum gradient foaming and online closed-loop edge sealing. There are no exposed pores in the cross section, the water absorption rate is not higher than 0.5%, the flame retardant level reaches GB 8624-2012 B1-A level and there is no dripping or thick smoke at high temperature. The raw materials of the gradient reinforced core layer, by weight, include: 28-38 parts of bamboo fiber bundles reinforced by in-situ biological growth, 12-22 parts of wood fiber, 32-42 parts of heat-resistant modified PP / PVC blend resin, 6-10 parts of nano boron nitride, 4-7 parts of basalt chopped fiber, 0.8-1.6 parts of crosslinking agent, 1.2-2.2 parts of composite heat stabilizer, 5-9 parts of halogen-free intumescent flame retardant, 0.3-0.7 parts of antioxidant, and 1.0-1.8 parts of interface compatibilizer; The signal modulation layer includes two optional structures: Structure A: a frequency-selective surface functional layer with a periodic microstructure array, wherein the periodic microstructure array includes a cross-shaped, square ring, or complementary open ring structure, with a period size of 5-20 mm and a metallization layer thickness of 5-20 μm; Structure B: a microporous structure layer containing micropores with a diameter of 20-50 μm, a pore size of 5-10 μm, and a micropore distribution density of 1000-2000 pores / cm². 2 ; The self-healing surface coating contains bamboo tar repair agent encapsulated in microcapsules. The microcapsules have a particle size of 5-20 μm and the wall material is lignin sulfonate. The self-healing surface coating also contains photothermal conversion nanoparticles, which are graphene oxide or carbon nanotubes, with a mass fraction of 0.1-1%, used to trigger microcapsule rupture under near-infrared light to accelerate the repair process. Both the first and second interface compatibility layers are maleic anhydride-grafted polypropylene compatibility layers with a thickness of 0.08-0.15 mm. Both layers exhibit a gradient density distribution, with the density gradually decreasing outwards from the contact surface with the core layer, and the density gradient rate is 0.05-0.15 g / cm³. 3 / mm.
2. The reinforced bamboo-wood fiberboard according to claim 1, characterized in that, The nanocellulose whiskers in situ grown on the surface of the bamboo fiber bundles have an aspect ratio of 50:1 to 200:1, a diameter of 5-30 nm, a length of 500-3000 nm, and a grafting density of 10-50 whiskers / μm on the surface of the bamboo fiber bundles. 2 .
3. The reinforced bamboo-wood fiberboard according to claim 1, characterized in that, The basalt short-cut fibers are 1.5-3.5 mm in length and 6-12 μm in diameter, and are surface-modified with a silane coupling agent; the halogen-free intumescent flame retardant is a compound system of aluminum hydroxide, magnesium hydroxide and ammonium polyphosphate, with a compounding ratio of 2:2:
1.
4. A method for processing reinforced bamboo-wood fiberboard according to any one of claims 1-3, characterized in that, Includes the following steps: Step S1: In-situ biological growth enhancement treatment of bamboo fiber bundles Bamboo is steam-exploded to obtain oriented bamboo fiber bundles, which are then bio-activated in a complex enzyme system of cellulase and xylanase to generate active functional groups on the surface of the bamboo fiber bundles. The activated bamboo fiber bundles are then placed in a fermentation medium containing cellulose-producing bacteria and cultured statically at 25-35℃ for 3-10 days to allow bacterial cellulose to grow in situ on the surface of the bamboo fiber bundles to form nano-cellulose whiskers, thus obtaining surface-reinforced bamboo fiber bundles. Step S2: Raw material pretreatment and grading The surface-reinforced bamboo fiber bundles and wood fibers obtained in step S1 are dried until their moisture content does not exceed 0.8%. According to the ratios of 3:1, 2:1, and 1:1 for each layer of the gradient-reinforced core layer, surface-reinforced bamboo fiber bundles, wood fiber, heat-resistant modified PP / PVC blended resin, nano boron nitride, basalt short fiber, halogen-free intumescent flame retardant, and additives are mixed to obtain three sets of core layer mixtures. Step S3: Multi-layer co-extrusion molding The UV-resistant and wear-resistant composite surface material, the three core layer mixtures, the low-expansion stable bottom layer material, the first interface compatibility layer material, and the second interface compatibility layer material were added to six extruders respectively. The plasticizing temperature of each extruder was controlled as follows: surface layer 185-200℃, core layer 175-190℃, bottom layer 180-195℃, and interface compatibility layer 180-190℃. Through a multi-layer co-extrusion die, the surface layer, the first interface compatibility layer, the gradient-reinforced core layer, the second interface compatibility layer, and the bottom layer were compounded in a top-to-bottom order to achieve integral extrusion. The die temperature was controlled at 182-192℃. Step S4: Vacuum gradient foaming and shaping The extruded sheet is fed into a vacuum gradient foaming chamber, where segmented temperature-controlled foaming is used. The foaming temperature is 170-175℃, 160-165℃, and 150-155℃ from the inlet to the outlet, respectively, while the vacuum degree is controlled between -0.07 and -0.09 MPa, so that the core layer forms uniform closed-cell microbubbles and honeycomb reinforcing ribs. It is then sent to a cooling and shaping machine, where segmented cooling is used to eliminate internal stress, and the cooling temperature is gradually reduced from 25℃ to 15℃. Step S5: Online closed-loop edge sealing The hot-press melting edge sealing process is used to wrap and seal the edges of the board in a closed loop. The sealing temperature is 200-210℃ and the pressure is 0.3-0.5MPa to ensure that there are no exposed pores on the cross-section of the board. Step S6: Signal modulation layer processing Based on design requirements, one of the following methods can be used to process the signal modulation layer on the surface of the board: Method A: A periodic microstructure array is prepared on the release film by printing or electroplating process, and then bonded to a predetermined position on the surface of the board during co-extrusion molding in step S3. After molding, the release film is peeled off to form a frequency-selective surface functional layer. Method B: After step S5, a microporous structure is processed on the surface of the board using laser engraving technology. The laser power is 5-8W and the scanning speed is 10-15 mm / s to form a microporous structure layer. Step S7: Apply self-healing surface coating Bio-based coatings containing microencapsulated bamboo tar repair agents and photothermal conversion nanoparticles are sprayed or rolled onto the surface of the board, with a coating thickness of 50-150 μm, and dried and cured at 40-60℃. Step S8: Surface modification and post-treatment The surface of the board is coated with nano-silica and then UV cured. The curing time is 30-60 seconds, and the UV intensity is 80-100 mW / cm². 2 Then, the product is cut and inspected according to specifications to obtain the finished product.
5. The processing method of the reinforced bamboo-wood fiberboard according to claim 4, characterized in that, In step S1, the steam explosion treatment pressure is 1.5-2.5 MPa, the pressure holding time is 3-8 minutes, and the pressure is released instantly; in the composite enzyme system, the cellulase activity is 5000-10000 U / g, and the xylanase activity is 2000-5000 U / g; the cellulose-producing bacteria are *Acetobacter xylinum* or *Agrobacterium*.
6. The processing method of the reinforced bamboo-wood fiberboard according to claim 4, characterized in that, In step S4, the foaming time in the vacuum gradient foaming chamber is 8-12 min, and the closed-cell rate is not less than 95%; in step S5, the width of the online closed-loop edge sealing is 1-2 mm, and the bonding strength between the edge sealing layer and the board body is not less than 2.0 MPa; in step S8, the amount of nano-silica spraying is 5-8 g / m². 2 .
Citation Information
Patent Citations
Coating nano antimicrobial material surface layer edge-trimming plate material and its making method
CN101190582A
Natural bamboo fibers modified by nano-cellulose whiskers and preparing method of natural bamboo fibers
CN106283793A
Composite cellular board based on continuous fiber reinforcement and preparation method thereof
CN120461949A
